Export and FDI in Asian countries: panel causality analysis - Abbas Rezazadeh Karsalari; Mohsen Mehrara; Maysam Musai (Hyperion Economic Journal, 2013)
The FDI of Multinational Companies (MNCs) can be export-oriented or market-oriented, intended to capture the international or local markets respectively. Since the MNCs have better export performance than local firms, in case of export-oriented FDI, this would lead local firms to mimic foreign firms in the same way. On the other hand, the reverse causality running from exports to FDI can also exist. It is argued that FDI is attracted to countries with a higher trade potential both in terms of imports and exports. This paper investigates the causal relationship between Foreign Direct Investment (FDI) and exports in 40 Asian countries by using panel unit root tests and panel cointegration analysis for the period 1970-2010. The results show a strong causality from exports to FDI in these countries. Moreover, FDI does have significant effects on export in short- and long-run. So, the findings imply bidirectional causality between foreign direct investment and export in these countries.